A Conceptual Framework for Designing Virtual Environments for Stress Therapy - Zaharuddin F.A.; Ibrahim N.; Yusof A.M. (MDPI, 2023)
Virtual reality for stress therapy has been shown to be effective in reducing stress. However, the majority of the existing studies have only focused on investigating the effectiveness of virtual reality application as a stress reduction tool. Limited information was communicated on how the virtual environments used were designed. Existing design frameworks which may potentially be used as a reference turned out to be providing general guidelines and were not specifically developed for designing a virtual environment for stress therapy. The frameworks were also found to focus on either improving psychological well-being or virtual reality design respectively. To address the identified gap, this study proposed a framework for designing virtual environments for stress therapy. The framework incorporates design requirements from a psychological and information technology point of view. In addition, the framework also highlights the design elements that were specifically needed to design a virtual environment to reduce stress. This paper hence describes the framework and discusses the framework evaluation. Four methods, including (i) questionnaire, (ii) physiological measures, (iii) experiment and (iv) interview were used to evaluate the (i) effectiveness, (ii) usability, (iii) ease of use and (iv) usefulness of the system that implemented the concept of the framework in reducing stress. In addition, the methods were also used to assess the usefulness of the design elements listed in the framework to reduce stress. The results of the evaluation indicated that the system was (i) effective, (ii) usable, (iii) useful and (iv) easy to use to reduce stress. The results also showed that the proposed design elements were useful in aiding the stress-reduction process. As all the results returned positive findings, the framework was thus considered appropriate and suitable to be used as a guideline for designing virtual environments for stress therapy. 2022 by the authors.